(untitled) (Research, Society and Development, 2021)
The bacterium Serratia marcescens is one of the species that produces prodigiosin, a red pigment with characteristics of interest in the pharmaceutical, food and textile areas. The aim of this study was to evaluate the effect of different nutritional parameters, and identify those that positively influence cell growth and pigment production in a species of Serratia marcescens isolated from a legume nodule. Initially, the tests were carried out in submerged fermentation using Luria Bertani broth (LB), being modified for the evaluation of different sources of carbon, nitrogen, temperatures and pHs. Sample readings were taken between 24 and 72 hours, measuring cell growth by optical density (OD) at 600 nm in a 96-well microplate and pigment production was performed by extracting the metabolite with the aid of methanol and subsequent reading in a spectrophotometer at 470 nm. As a result, the highest biomass production was obtained using sucrose and glucose as carbon sources, NH4Cl as nitrogen source, at a temperature of 25 °C and pH varying between 6.0 and 7.0. The highest pigment production occurred when soluble starch was used as a carbon source and NH4Cl as a nitrogen source, at a temperature of 25 °C and pH 8.0. We conclude that from the results obtained by evaluating the different nutritional parameters, it was observed that carbon sources such as sucrose and glucose stimulate the cell growth of Serratia marcescens but significantly inhibit the production of pigments, as well as the variation in pH levels.